2022
DOI: 10.1080/02699206.2022.2074310
|View full text |Cite
|
Sign up to set email alerts
|

Lexical tone perception and production in Cantonese-speaking children with childhood apraxia of speech: a pilot study

Abstract: Introduction: Childhood apraxia of speech (CAS) is a paediatric motor speech disorder. We investigated the lexical tone perception and production abilities of children with CAS and the relationships between the two. Methods: Three children with CAS, aged between 3;7 and 5;8, were given the Cantonese Tone Identification Test (CANTIT) and the Hong Kong Cantonese Articulation Test (HKCAT) for assessment of tone perception and production, respectively. Accuracy and error patterns were investigated based on their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The results will promote the standard of CAS diagnosis in Cantonese speakers from reliance on expert perceptual judgment based on a list of clinical features [ 41 ] to a combination of perceptual judgment and quantitative data. In addition, the short administration time of the measures proposed in this study (ie, approximately 15-20 minutes per measure) will provide clinicians with quick and accurate methods for CAS diagnosis in Cantonese speakers than approximately 2 hours of comprehensive assessment [ 18 , 41 , 42 ] of speech motor skills reported in the literature. Moreover, the results of this study will provide the basis for further investigations of pitch-variation skills in children with CAS who speak other tonal languages (eg, Mandarin, Vietnamese, and Thai) as well as in children with CAS who speak nontonal languages (eg, English).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results will promote the standard of CAS diagnosis in Cantonese speakers from reliance on expert perceptual judgment based on a list of clinical features [ 41 ] to a combination of perceptual judgment and quantitative data. In addition, the short administration time of the measures proposed in this study (ie, approximately 15-20 minutes per measure) will provide clinicians with quick and accurate methods for CAS diagnosis in Cantonese speakers than approximately 2 hours of comprehensive assessment [ 18 , 41 , 42 ] of speech motor skills reported in the literature. Moreover, the results of this study will provide the basis for further investigations of pitch-variation skills in children with CAS who speak other tonal languages (eg, Mandarin, Vietnamese, and Thai) as well as in children with CAS who speak nontonal languages (eg, English).…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that an understanding of CAS in Cantonese speakers is lacking. Even experienced speech-language pathologists are not confident in using criteria for making a differential diagnosis of CAS in Cantonese-speaking children [ 44 ]. The challenge of making such an accurate diagnosis will be ameliorated through the dissemination of these results.…”
Section: Discussionmentioning
confidence: 99%
“…The existing understanding of CAS is mainly based on English and Dutch speakers, but the literature about CAS in children who speak other languages is growing. For example, the genetic and neural bases of CAS have been investigated in Chinese [29] and Italian [30]; clinical features or speech performance have been explored in Arabic [31], Cantonese [32,33], Mandarin [34], and French [35]; assessment tests or diagnostic checklists have been developed for Arabic [36], Brazilian Portuguese [37], Danish [38], and Swedish speakers with CAS [39]; and the treatment efficacy of different approaches has been examined in speakers of Brazilian Portuguese [40,41], Cantonese [42], German [43], Italian [44], Korean [45], Mandarin [46], Spanish [47], and Turkish [48].…”
Section: Cas In Other Languagesmentioning
confidence: 99%
“…In particular, lexical tone errors and difficulty in perceiving tones were identified as clinical features that had never been reported for English speakers with CAS. Further investigation of tone perception and production skills, as well as the development of a potential diagnostic tool, were then carried out, resulting in an increased understanding of CAS in Cantonese, and probably other tonal languages [32,33].…”
Section: Importance Of Survey Studiesmentioning
confidence: 99%
See 1 more Smart Citation